Eksplicitna poetika Rista Ratkovića - Vojičić-Komatina, Olga (Slavistična revija, 2015)
Based on Ratković's notions about poetry and on his ideas about the function and nature of art during the spread of avant-garde movement, today's researchers of his work can adequately reconstruct his very intricate, yet transformative thought. The overall Ratković's essayistic discourse, eclectically incorporated in the work of Esejistika i kritika Essays and Criticism, is a fundamental testimony of all poetic variations frequently found in his poetry, as his literary expression varies from neo-romanticism through Zenitism, Dadaism, and surrealist reflection, to the final and definitive commitment to social realist profile of his poetic texts.
Keywords: anti-aesthetic; antiestetika; Dadaism; dadaizem; esejistika; essayistic discourse; literarni kritiki; literary critics; moral issue of art; morala; morality; nadrealizem; Ratković, Risto, 1903-1954; srbska književnost; Surrealism; tradicionalna metrika; traditional metrics; Zenitism; zenitizem